Effectiveness of Interactive Gamification-Based Learning Media: A Development Study Using DDR and the MDA Framework - Kania Athallah Yuhen; Maria Seraphina Astriani (JTP - Jurnal Teknologi Pendidikan, 2026)
The problem of monotonous and conventional teaching methods in English classes, particularly in teaching Parts of Speech, remains a persistent issue that often leads to low student motivation and poor cognitive achievement. Therefore, the research question guiding this study is: how effective is the interactive gamification-based learning media for Parts of Speech, developed using the DDR–MDA framework, in improving junior high school students’ cognitive learning outcomes. Accordingly, this study aims to design and develop an interactive gamification-based learning medium for junior high school students as an innovative solution. The method used is Design and Development Research (DDR), integrated with the MDA (Mechanics, Dynamics, Aesthetics) framework. The development stages include needs analysis through literature review and field study, lesson plan (RPP), material, and storyboard design, prototyping with expert validation, implementation using a pretest–posttest control group experimental design, and evaluation with descriptive and inferential analysis. The research subjects were 60 ninth-grade students of SMP Negeri 2 Bojongsoang, divided into experimental and control groups. Research instruments included validation sheets (LORI), pretest–posttest questions, and student response questionnaires based on TAM. Data analysis was conducted using descriptive statistics (mean, median, SD), assumption tests (Shapiro-Wilk and Levene’s Test), paired t-test and independent t-test, effect size calculation (Cohen’s d), and N-Gain accompanied by qualitative interpretation. The results showed that expert validation rated the medium as “very good.” The experimental group achieved a significantly higher posttest average score compared to the control group (t = 3.545; p < 0.001). The effect size was categorized as large, and the N-Gain indicated moderate improvement. Student responses through TAM were also very positive (classified as “very good”). These findings confirm that gamification is effective in improving learning outcomes, motivation, and technology acceptance in English language learning.